Intention to be screened for Alzheimer's disease in nondemented older adults: Integrated behavioral model and self-efficacy as mediation effect. Issue 6 (17th August 2020) - Park, Juyoung; Tolea, Magdalena; Besser, Lilah; Galvin, James
ABSTRACT: The study explored factors associated with intention to be screened for Alzheimer's disease (AD). The study also examined whether self-efficacy mediates the relationship between knowledge about screening and the intention to be screened for AD. A population-based, random-digit dialing survey was performed and 1, 043 responses were collected from a sample of nondemented persons (50 years or older) living in urban, suburban and rural areas in a Midwestern state. The findings showed that participants who were younger and who had higher levels of (a) perceived benefits and barriers, (b) social support and (c) self-efficacy reported higher levels of intention to be screened for AD. Older adults with positive life orientation reported greater intention to be screened for AD, whereas depressed participants were more likely to report a plan to be screened for AD. Self-efficacy mediated the relationship between knowledge about screening and intention to be screened. Older adults were more likely to report intention to be screened when they had positive attitudes about the screen and believed that they could receive the screen. The intention to be screened for AD could serve public awareness by defining effective ways to assist older adults to seek a cognitive screen.